2017
DOI: 10.3926/ic.986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of in-store and out-of-store creative advertising strategies on consumer attitude and purchase intention

Abstract: Purpose: With regard to the fact that people usually try to avoid repetitive and boring advertisements, creativity as the heart of advertising effectiveness has a significant role in drawing their attention. On this basis, the present study attempts to evaluate the influence of creative advertising strategies by comparing "in-store" and "out-of-store" creative advertisements.Design/methodology: This research has been conducted in Tehran (capital of Iran) and 588 volunteers randomly participated in the survey s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…looking at the storefront). Our findings are also in line with Sameti and Khalili (2017), who found that out-of-store stimuli were able to evoke higher levels of store interest than in-store stimuli.…”
Section: Discussion and Research Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…looking at the storefront). Our findings are also in line with Sameti and Khalili (2017), who found that out-of-store stimuli were able to evoke higher levels of store interest than in-store stimuli.…”
Section: Discussion and Research Implicationssupporting
confidence: 92%
“…looking at the store and its merchandise) when the HSR is located outside the store than when it is placed inside. Moreover, based on the research of Sameti and Khalili (2017), out-of-store stimuli have been proven to generate a better overall (brand) awareness than in-store stimuli, making the outside placement of the robot the better option to increase store interest. Therefore, we hypothesize the following:…”
Section: Stopping Power: Drawing Attentionstopping Passersbymentioning
confidence: 99%
“…Studies have shown that ethnic consumers notice and have a positive response to ethnic cues in advertisements (Dimofte et al, 2003; Khan et al, 2015; Torres and Luna-Nevarez, 2012). By raising the salience of ethnic consumers, cultural cues such as ethnic language, symbol or model are effective in influencing ethnic consumers (Appiah and Liu, 2009; Chang, 2014; Cui et al, 2012; Sameti and Khalili, 2017). For example, Green (1999) shows that the presence of an ethnic spokesperson in an advertisement raised ethnic consumers’ liking for the advertisement as well as the advertised product.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…and "What kinds of advertising should be done?" have been raised by practitioners and researchers (Sameti & Khalili, 2017). In this sense, it is worth examining how airline advertising can be more effective and drive consumers to purchase.…”
Section: Introductionmentioning
confidence: 99%
“…The S-O-R model provides a useful account of how advertising creativity affects purchase intention. Although this relationship has been studied by many researchers in the extant literature (Idris et al, 2020;Sameti & Khalili, 2017;Shirkhodaee & Rezaee, 2014), no research has been found that surveyed the impact of advertising creativity on purchase intention in the airline industry. In fact, the effect of advertising creativity on purchase intention is related to the elaboration likelihood model (ELM).…”
Section: Introductionmentioning
confidence: 99%